piggyBac-Based Non-Viral In Vivo Gene Delivery Useful for Production of Genetically Modified Animals and Organs - Masahiro Sato; Emi Inada; Issei Saitoh; Satoshi Watanabe; Shingo Nakamura (MDPI AG, 2020)
In vivo gene delivery involves direct injection of nucleic acids (NAs) into tissues, organs, or tail-veins. It has been recognized as a useful tool for evaluating the function of a gene of interest (GOI), creating models for human disease and basic research targeting gene therapy. Cargo frequently used for gene delivery are largely divided into viral and non-viral vectors. Viral vectors have strong infectious activity and do not require the use of instruments or reagents helpful for gene delivery but bear immunological and tumorigenic problems. In contrast, non-viral vectors strictly require instruments (i.e., electroporator) or reagents (i.e., liposomes) for enhanced uptake of NAs by cells and are often accompanied by weak transfection activity, with less immunological and tumorigenic problems. Chromosomal integration of GOI-bearing transgenes would be ideal for achieving long-term expression of GOI. piggyBac (PB), one of three transposons (PB, Sleeping Beauty (SB), and Tol2) found thus far, has been used for efficient transfection of GOI in various mammalian cells in vitro and in vivo. In this review, we outline recent achievements of PB-based production of genetically modified animals and organs and will provide some experimental concepts using this system.